A case study of change and innovation: Addiction and Mental Health Kingston, Frontenac, Lennox, and Addington. Issue 5 (September 2021) - Swan, Bruce Harry; Dean, Betty Jo; Ravnaas, Carol
Addiction and Mental Health Services of Kingston, Frontenac, Lennox, and Addington is emerging from years of fractured leadership and operational experiences to a new era of promise—with lessons learned along the way. A case study of change and innovation describes the journey Addiction and Mental Health Services of Kingston, Frontenac, Lennox, and Addington has been on since 2020, including making a transition from a Chief Executive Officer to a Joint Executive Leadership model to meet organizational needs, and adopting an approach to governance that is collaborative and integrates existing stakeholder governance representatives to mirror the current provincial Ontario Health Team vision of service.